The Mediating Role of Forgiveness and Self-Efficacy in the Relationship Between Childhood Maltreatment and Treatment Motivation Among Malaysian Male Drug Addicts - See Mey, Loy; Khairudin, Rozainee; Tengku Muda, Tengku Elmi Azlina; Abdullah @ Mohd Nor, Hilwa; Kamaluddin, Mohammad Rahim (Frontiers in Psychology, 2022)
Studies have reported high rates of childhood maltreatment among individuals with drug addiction problems; however, investigation about the potentially protective factors to mitigate the effects of maltreatment experiences on motivation to engage in addiction treatment has received little attention. The current study aims at exploring the mediating effects of forgiveness and self-efficacy on the association between childhood maltreatment and treatment motivation among drug addicts. 360 male drug addicts (mean age = 33.34, SD = 7.25) were recruited from three mandatory inpatient rehabilitation centers in Malaysia. Participants completed a package of self-report questionnaires including measures of childhood maltreatment experiences, forgiveness, self-efficacy, and motivation for treatment. The analysis conducted using the structural equation model (SEM) revealed childhood maltreatment significantly predicted lower treatment motivation, while forgiveness played a fully mediating role regarding the effect of childhood maltreatment on treatment motivation. However, there were no significant changes in childhood maltreatment in response to self-efficacy, yet a significant positive relationship was found between self-efficacy and treatment motivation. In conclusion, these findings suggest that combining the element of forgiveness in treatment programs appears to benefit the drug addicts with childhood maltreatment history.